NEW MEDIA AND MODEL OF NEWS REPORTING IN NORTH SUMATERA, INDONESIA - Hendra Harahap; Yovita Sabarina; Fatma Wardy Lubis (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2021)
Studies in the presence of new media and its relationship with conventional media recently could be mapped into three trends. Firstly, studies in media competition between traditional and online media. These studies, generally put online media both in a position that is superior to traditional media, and also as a complement to the existence of traditional media. Second, studies that explore patterns of online and print media consumption that show dualism in the use of media by the public. These study highlight how consumers use online and print media together and are complementary (complementary models). Third, studies that look at the impact of social media on journalism practices that give a new character to the system and mechanism of media work. This article will explain the relationship between the growth of new media, media competition and its impacts on the mode of news reporting in North Sumatra, Indonesia. This article starts with the assumption that the massive expansion of new media can also have a positive impact on the industry and media organizations.